2011
DOI: 10.1016/j.chaos.2011.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics on small-world neuronal networks: The roles of two types of time-delayed coupling

Abstract: We investigate temporal coherence and spatial synchronization on small-world networks consisting of noisy Terman-Wang (TW) excitable neurons in dependence on two types of time-delayed coupling:For the former case, we show that time delay in the coupling can dramatically enhance temporal coherence and spatial synchrony of the noise-induced spike trains. In addition, if the delay time τ is tuned to nearly match the intrinsic spike period of the neuronal network, the system dynamics reaches a most ordered state, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 66 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Undoubtedly, interactions between elements are always non-instantaneous in coupled systems. For example, time delays are up to 80 ms for propagation through the coupled cortical networks [31]. Moreover, the effect of the sinoatrial node signal reaches the atrioventricular node after about 0.2 s in heart pacemakers [32].…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, interactions between elements are always non-instantaneous in coupled systems. For example, time delays are up to 80 ms for propagation through the coupled cortical networks [31]. Moreover, the effect of the sinoatrial node signal reaches the atrioventricular node after about 0.2 s in heart pacemakers [32].…”
Section: Introductionmentioning
confidence: 99%
“…Touboul et al revealed a novel anti-resonance phenomenon, and proposed a new hypothesis for the eciency of high-frequency stimulation in Parkinson's disease [30]. There are many other works having been done about a small-world network of neurons excited by noise [31][32][33][34], and Gaussian noise is chosen there. Many properties of Gaussian noise are not applicable to α-stable noise due to the heavy tails.…”
Section: Introductionmentioning
confidence: 99%